(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper examines the career aspirations and self efficacy of underachievers. The study aims to evaluate that impact of counseling on career aspirations and self efficacy levels of the underachievers. Data was collected from sample of 140 students of both the genders, with an average age of 15 years. The sample students of class IX were selected from different senior secondary schools of South Delhi. Self constructed career aspiration tool and self-efficacy scale by Ralf Schwarzer and Malthias Jerusalem was used for the data collection. The data will be analyzed quantitatively using descriptive statistics and t-test to find significance of mean difference of self-efficacy and career aspirations of underachievers of control and experimental group. The analysis of the data indicated the significant difference between the mean scores of career aspiration (t= 0.09) and self efficacy scores (t=38.17) in the pre test and post test of the samples was found. Career development in children largely involves learning about the world of work from family members, peers, and classroom exploration in elementary school. For children of economic disadvantage, a lack of resources, restricted access to information, and limited experience observing positive role models employed in a variety of work environments may curtail their ability to envision career attainment.